Study on the Modeling of Rainfall Interception Calculation Using Parallel Computation Systems - Fadhli, Mulkan (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2015)
The researches on mathematical modeling are getting more complexes and have been applied to various fields, and hydrology is one of the fields that use mathematical modeling on interception. Numerous mathematical models have been developed. Rainfall interception modeling performed to predict the overflow of water after rain occurs, so it can be used for disaster mitigation in regional development. Calculation of rainfall interception model on land (watershed) which is very spacious and has leafy trees, (eq. garden) required high computational resources (time and computer system). This kind of problems can be overcome by developing the model into parallel computation. In this study, interception modeling on parallel computation systems.Keywords: Interception Modeling, Parallel Computation, Modelling